2014
DOI: 10.1155/2014/410142
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Tuberculosis or Autoimmune Pancreatitis

Abstract: Introduction. Isolated pancreatic and peripancreatic tuberculosis is a challenging diagnosis due to its rarity and variable presentation. Pancreatic tuberculosis can mimic pancreatic carcinoma. Similarly, autoimmune pancreatitis can appear as a focal lesion resembling pancreatic malignancy. Endoscopic ultrasound-guided fine needle aspiration provides an effective tool for differentiating between benign and malignant pancreatic lesions. The immune processes involved in immunoglobulin G4 related systemic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…PCR assay is helpful in diagnosis, and laparotomy can be avoided. Ayesha et al [69] and Chatterji et al [60] utilized PCR assay in conjunction with EUS-guided FNAC to diagnose pancreatic tuberculosis. PCR assay in conjunction with other non-invasive modalities is helpful in diagnosing pancreatic tuberculosis.…”
Section: Role Of Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR assay is helpful in diagnosis, and laparotomy can be avoided. Ayesha et al [69] and Chatterji et al [60] utilized PCR assay in conjunction with EUS-guided FNAC to diagnose pancreatic tuberculosis. PCR assay in conjunction with other non-invasive modalities is helpful in diagnosing pancreatic tuberculosis.…”
Section: Role Of Polymerase Chain Reactionmentioning
confidence: 99%
“…Careful monitoring for drug-induced hepatitis may obviate fatality. For follow-up and guiding clinicians regarding complete resolution and duration of therapy, CT imaging is helpful [69]. In a retrospective study by Kim et al [71], out of 42 patients with pancreatic tuberculosis, only 1 patient had progressive disease on CT imaging.…”
Section: Treatmentmentioning
confidence: 99%
“…[9][10][11] Not only does pancreatic tuberculosis mimic pancreatic cancer, it also causes diagnostic confusion with other pancreatic disorders like pancreatic cystic neoplasms, chronic pancreatitis, and autoimmune pancreatitis. 7,[12][13][14][15][16][17] Because the disease is uncommon even in the regions endemic for tuberculosis, the diagnosis is often missed or delayed in most cases. Most reports of pancreatic tuberculosis indicate a preponderance of males in the reported cases except for two reports from China and South Korea.…”
Section: Clinical Presentation and Laboratory Findingsmentioning
confidence: 99%
“…The initiation phase of the therapy consists of intensive therapy with multiple drugs (rifampin, isoniazid, pyrazinamide, and ethambutol) given daily for 2 months, and this is followed by a continuation phase of at least 4 months with rifampin and isoniazid. The usual dosages for rifampin, isoniazid, pyrazinamide, and ethambutol are 10 mg/kg/day (8-12 mg/kg/day), 5 (4-6) mg/kg/day, 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) mg/kg/day, and 15 (15)(16)(17)(18)(19)(20) mg/kg/day respectively. In contrast to other forms of tuberculosis like pulmonary and intestinal, there is no data regarding use of intermittent therapy for pancreatic tuberculosis.…”
Section: Treatment Of Pancreatic Tuberculosismentioning
confidence: 99%
“…Previous reports have shown that open surgery or laparotomy is often necessary to confirm such diagnoses (4)(5)(6). Endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNAB) is becoming increasingly established as a minimally-invasive alternative to open surgery for the purpose of diagnostic confirmation; more recently, the utility of EUS-FNAB in the diagnosis of pancreatic TB has also begun to be reported as well (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%